تحليل العلاقة بين تحسين الأداء المالي للمصارف و جذب الودائع: بحث تطبيقي في عينة من المصارف العراقية الخاصة (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The banking performance and deposits attraction are considered to be of great importance in banks management, also the banking  performance is one of the indications that measure the ability of satisfying and full fill the banks  goals and the range of approach and move away from those goals, Also there are some important factors that affects on deposits, such as financial performance ,The aim of the research is to measure and analyses the banking performance and showing its effective impact and its relation in attracting deposits.For the satisfaction of the research goals a smple was selected from the Iraqi banks which represented in five private banks were their data been analyzed between the periods 2009 to 2013 ,the aim was to find the effect and the relation between  the independent variable which is financial performance for banks and dependent variable which represented by banks deposits.